2019
DOI: 10.1084/jem.20190860
|View full text |Cite
|
Sign up to set email alerts
|

B cell tolerance and antibody production to the celiac disease autoantigen transglutaminase 2

Abstract: Autoantibodies to transglutaminase 2 (TG2) are hallmarks of celiac disease. To address B cell tolerance and autoantibody formation to TG2, we generated immunoglobulin knock-in (Ig KI) mice that express a prototypical celiac patient–derived anti-TG2 B cell receptor equally reactive to human and mouse TG2. We studied B cell development in the presence/absence of autoantigen by crossing the Ig KI mice to Tgm2−/− mice. Autoreactive B cells in Tgm2+/+ mice were indistinguishable from their naive counterparts in Tgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
(93 reference statements)
1
45
0
Order By: Relevance
“…The highest relative risks are for T cell NHL, but also B cell NHL are described in CD. This is in accordance with the relevance of B cells in CD-pathogenesis, as antigen-presenting cells and immunoglobulin producers [43]. The most likely explanation for this association between lymphoma and CD is chronic inflammation.…”
Section: Celiac Disease and Risk Of Malignanciessupporting
confidence: 87%
“…The highest relative risks are for T cell NHL, but also B cell NHL are described in CD. This is in accordance with the relevance of B cells in CD-pathogenesis, as antigen-presenting cells and immunoglobulin producers [43]. The most likely explanation for this association between lymphoma and CD is chronic inflammation.…”
Section: Celiac Disease and Risk Of Malignanciessupporting
confidence: 87%
“…Early studies implicating TG2 in celiac disease pathogenesis showed that jejunal tissue samples taken from individuals with treated and untreated celiac disease demonstrated increased TG2 activity compared to healthy controls [ 47 ]. While the prevailing hypothesis has been that TG2 activity occurs in the lamina propria [ 48 ], recent studies have shown that active TG2 can also be released into the lumen as a result of standard shedding of the gut epithelium [ 49 ], where anti-TG2 B cells may develop to produce autoantibodies against TG2 [ 49 , 50 ]. Catalytically active TG2 plays an important role in the presentation of gliadin as an antigen; it catalyzes the deamidation of glutamine to glutamic acid within gliadin peptides [ 48 ], resulting in a change in charge of the peptide from neutral to negative [ 48 , 51 ].…”
Section: Celiac Disease Pathogenesismentioning
confidence: 99%
“…It was established that increased tTG2 activity leads to autoimmune reaction and GSE, i.e., CD in genetically-predisposed individuals [34][35][36]. Besides gluten digestion, tTG-mediated glutamine deamidation can, in some celiac patients, lead to the aggregation of cerebral β-amyloid, one of the hallmarks of neurodegeneration in people with PD, HD, and AD [37][38][39][40][41][42].…”
Section: Mechanisms Of Dietary Gluten-induced Neuropathymentioning
confidence: 99%